Primary neuroleptospirosis. Issue 911 (1st September 2001) - Panicker, J N; Mammachan, R; Jayakumar, R V
Abstract : Leptospirosis is an important zoonosis of worldwide distribution. It is uncommon for leptospirosis to present as a primary neurological disease. In this study of patients who presented with an acute neurological disease, and who were subsequently found to have leptospirosis, aseptic meningitis was the commonest manifestation. The other presentations were myeloradiculopathy, myelopathy, Guillain-Barré syndrome-like presentation, meningoencephalitis, intracerebral bleed, cerebellar dysfunction, iridocyclitis, and tremor/rigidity. Treatment consists of antibiotics, crystalline penicillin being the drug of choice, which reduces the course of illness if given early. The role of steroids is controversial. The prognosis after primary neuroleptospirosis is generally good but altered sensorium and seizures herald a worse prognosis.